Effect of Inclusion of Black Pepper Powder as Natural Feed Additive on the Performance of Japanese quail - Veeranki, Sri Divya; Rao, D Srinivas; Rao, E. Raghava (Indian Journal of Animal Nutrition, 2020)
The study was conducted to determine the effect of inclusion of black pepper (BP) powder in the diet on production performance, nutrient digestibility and carcass characteristics of Japanese quail. One hundred and fifty, day old quail chicks were randomly allotted into five experimental groups, each with 3 replicates of 10 chicks and were offered respective diets for 5 weeks. BP was ground and is included at 0% (T1; Control), 0.25 (T2), 0.50 (T3), 0.75 (T4) and 1.0 (T5) percent levels in iso-caloric and iso-nitrogenous broiler quail diets to meet the nutrient requirements as per NRC, 1994. Resulted indicated increased body weight gain (P